Nematode-induced demasculinization of Nearctic Dolichopodidae (Diptera) with five new synonyms - Runyon, Justin B. (Zootaxa, 2022)
Demasculinization, the reduction of male sexual characters due to parasitic nematode infection, is described in Nearctic Dolichopodidae. Five species are confirmed to be demasculinized (3 species of Dolichopus Latreille and 1 species each of Rhaphium Meigen and Tachytrechus Haliday) by nematodes in two families (apparent Mermithidae and Parasitylenchidae). The following nematode-infected males were inadvertently described as new species and are here proposed as synonyms: Dolichopus hurleyi Runyon, 2008 = D. dorycerus Loew, 1864, syn. nov.; Dolichopus frosti Runyon, 2008 = D. sincerus Melander, 1900, syn. nov.; Tachytrechus boharti Harmston, 1968 = T. sanus Osten Sacken, 1877, syn. nov.; Tachytrechus duplicatus Harmston, 1972 = T. sanus Osten Sacken, 1877, syn. nov.; Tachytrechus mchughi Harmston, 1972 = T. sanus Osten Sacken, 1877, syn. nov. A conspectus is presented of the scope of taxonomic problems caused by nematodes in Nearctic Dolichopus and Tachytrechus, which suggests that ten additional names in Dolichopus could be based on infected specimens. Guidelines are provided for recognizing nematode infection to avoid erroneous species descriptions.